2009
DOI: 10.1098/rspb.2009.1767
|View full text |Cite
|
Sign up to set email alerts
|

Brooding fathers, not siblings, take up nutrients from embryos

Abstract: It is well known that many animals with placenta-like structures provide their embryos with nutrients and oxygen. However, we demonstrate here that nutrients can pass the other way, from embryos to the parent. The study was done on a pipefish, Syngnathus typhle, in which males brood fertilized eggs in a brood pouch for several weeks. Earlier research has found a reduction of embryo numbers during the brooding period, but the fate of the nutrients from these 'reduced' embryos has been unknown. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…Although the current study found no effect of male size on the uptake of either nutrient, this might be due to large males receiving a lower dose relative to their body size. The value of amino acids is further indicated by a paternal ability to take up such nutrients of maternal origin from eggs in the brood pouch (Sagebakken et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study found no effect of male size on the uptake of either nutrient, this might be due to large males receiving a lower dose relative to their body size. The value of amino acids is further indicated by a paternal ability to take up such nutrients of maternal origin from eggs in the brood pouch (Sagebakken et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A preference for MHCcompatible mates, associated with the lack of detectable visual cues associated with heat-killed Vibrio infection, may mask or override a preference for uninfected females in our experiment. Furthermore, because males are in control over egg development and can actively abort and absorb eggs of unattractive females (Paczolt and Jones 2010;Sagebakken et al 2010), post-copulatory processes can correct male mate decisions. Therefore, mate preference patterns identified here may not reflect the whole complexity of mate choice behavior.…”
Section: Mate Preference Of Unchallenged Fishmentioning
confidence: 99%
“…Recent studies that focused on various aspects of post‐copulatory sexual selection in syngnathids indicate that interesting phenomena are occurring after mating. For example, males in S. typhle have the ability to absorb nutrients from the embryos in their pouches, which sets the stage for sexual conflict (Sagebakken et al , 2010). Results from an experiment in S. scovelli further suggest that post‐copulatory sexual selection and sexual conflict may be occurring (Paczolt & Jones, 2010).…”
Section: Parentage Sexual Selection and Mating Behaviour In Syngnathmentioning
confidence: 99%